Solutions for Preventing Patient Falls in Hospitals: A Scoping Review - Marziyeh Najafi; Roya Rajaee; Hojjat Rahmani; Behrooz Pouragha; Nazanin Sheikh Mohammadi; Ghasem Rajabi Vasokolaei (Tehran University of Medical Sciences, 2024)
Background and Aim: Patient falls are common in hospitals, leading to financial loss and potential harm to patients, staff, and the organization. They can often be prevented with proper planning. This study aims to identify strategies to prevent patient falls and provide evidence to develop safety initiatives. Materials and Methods: Our review used the Arksey and O'Malley scoping review model to identify strategies for preventing patient falls. We conducted searches with relevant keywords in the PubMed and Web of Science databases until May 25, 2024. In the final stage, we consulted with 18 experts using the Delphi method to gather their opinions. The data were analyzed using the thematic analysis method. Results: Out of the 4202 studies initially found, 19 articles were chosen. The solutions to prevent patient falls can be grouped into six general categories: planning (which includes quality improvement programs, establishment of patient safety culture, patient fall prevention guidelines and programs), physical space (involving patient room design and the location of treatment staff), equipment (such as monitoring and alarms, pressure sensors, and standard beds), human resources (including communication networks between nurses and other treatment staff, as well as factors like self-efficacy and responsiveness of nurses, and their motivation and job satisfaction), training (covering education and patient participation, training of nurses and treatment staff, and electronic training), and control of executive processes (involving evaluation of risk factors and process control). The highest level of agreement among the members was on the equipment dimension (9.76), and the lowest was on the human resources dimension (8.65). Conclusion: Patient falls are a common safety concern in hospitals and can be prevented with proper planning. Each hospital should use a combination of prevention methods tailored to its specific conditions.